Mineralogical, Chemical, and Geotechnical Characterization of Natural Clay for Ceramic Applications - Abbou Mohammed; Boumelik Zoheir; Semcha Abdelaziz (Civil Engineering Journal, 2026)
In the framework, the sustainable local development of the Adrar region is one of the largest in the Algerian Sahara. The Algerian government has launched a search for useful local substances to cover the need for building materials in the construction sector. However, the Algerian Sahara has a variety of mineral resources, including clays. This work aims to characterize and identify a natural Algerian clay from the Reggane basin (Paleozoic sedimentary basin) in southwestern Algeria. This is for use in the manufacture of ceramic products. For this, numerous analyses were carried out using techniques such as X-ray Diffraction (XRD) to determine the different crystalline mineral phases, X-ray Fluorescence (XRF) to identify the elemental composition, and Infrared Spectroscopy (FTIR) to study the molecular structure along with the geotechnical identification in order to better understand the main properties of this clay. The findings indicated that Reggane clay is silty and highly plastic (21.94-31.7). It contains a mixture of illite, kaolinite, and quartz, in very significant proportions, as well as hematite, orthoclase, and palygorskite. Furthermore, elemental chemical analyses were conducted, and the results showed that the main constituents of this clay are SiO₂ (58.19%-61.71%), Al₂O₃ (13.32%-13.50%), and Fe₂O₃ (6.13%-6.40%). These findings could eventually be used to target applications of this clay in the production of local fired materials.